2021
DOI: 10.1002/cjoc.202000543
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Flexible Supercapacitors Formed by Integrating Hydrogel with Functional Carbon Nanomaterials

Abstract: With the rapid development of the wearable electronics, the flexible supercapacitor with high energy density has attracted more and more attentions. From the viewpoint of outdoor and underwater application, this research tried to impart the superhydrophobicity to the flexible supercapacitors. The polyvinyl alcohol/HNO 3 hydrogel was utilized as the electrolyte, which could achieve self-healing capability without the freezing/thawing process. Both microscale graphene and nanoscale carbon nanotubes were utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…Be- sides, the maximum adsorption capacity using the D-R isotherm was obtained 34.62 mg/g. 40,41 In addition, the Gibbs free energy (ΔG°) using the Langmuir model was determined -5.112 KJ/mol, which indicates the spontaneity degree of the sorption process. Also, negative value of ΔG° shows a favorable sorption process.…”
Section: Equilibrium Study Of Adsorption Processmentioning
confidence: 99%
“…Be- sides, the maximum adsorption capacity using the D-R isotherm was obtained 34.62 mg/g. 40,41 In addition, the Gibbs free energy (ΔG°) using the Langmuir model was determined -5.112 KJ/mol, which indicates the spontaneity degree of the sorption process. Also, negative value of ΔG° shows a favorable sorption process.…”
Section: Equilibrium Study Of Adsorption Processmentioning
confidence: 99%
“…The hydrophobic powders were fabricated based on our previous research with small modification. [ 34‐35 ] First, 0.5 g of FAS was dissolved in 10 g of THF and the mixed solution was magnetically stirred for 2 h. Then, 0.5 g of MWCNTs and 0.3 g of graphene were sequentially added to form a paint‐like suspension. In order to ensure the uniform distribution of MWCNTs and graphene in the suspension, this suspension was treated by ultrasonic for 0.5 h and then magnetically stirred for 4 h. In the next step, the suspension was poured into an evaporating dish.…”
Section: Methodsmentioning
confidence: 99%
“…Research is shown that other aspects of employee behavior are important and depend on the effort of the staff members of the organization (Specht et al, 2007). Employee efforts to satisfy customers are more important than the capabilities they have previously received Wang et al (2021). Management should focus on the enhancement of staff effort.…”
Section: Mechanical Aspect Of Customer Experience Managementmentioning
confidence: 99%